The temporal variation in pesticide concentrations within matured French wines - Pieter Spanoghe; Jasmine De Rop; Lilian Goeteyn; Agnieszka Deja-Muylle; Hannah Vanderstappen; Lotte Neckebroeck; Dries Verhaegen; Pauline van den Hove; Joachim Neri; Erik Meers (PLoS ONE, 2025)
Numerous organizations worldwide are diligently working to regulate the composition of food products, with a particular focus on pesticide content. Each year, several substances are classified as hazardous to human health and subsequently banned from agricultural use. In this study, we address the age-old question: "Does wine improve with time?" from the context of pesticide composition. We gathered wine samples from renowned French winemaking regions, covering the years 1935 to 2000, to assess pesticide levels and identify specific substances. Our objective was to determine if any currently banned pesticides were present in these aged wines and whether the detected levels pose health risks under typical daily consumption patterns. Our findings revealed the presence of trace amounts of 21 different pesticides proceeding from Plant Protection Products (PPPs), in most of the wine samples, albeit at levels considered non-threatening to human health. Notably, one sample exhibited an alarmingly high concentration of carbaryl, surpassing toxic consumption thresholds. This study prompts discussions regarding the prioritization of pesticide testing in various products and whether stringent regulations should be upheld in the wine selling collectors sector.